PRlMARY GASTROINTESTINAL LYMPHOMAS - Esin ÖZYILKAN; Mehmet ARSLAN; Halis ŞİMŞEK and Burhan KAYHAN and Bülent SİVRİ and Gonca TUTAR and Gülten TEKUZMAN and Bedri UZUNALİMOĞLU and; n TELATAR (Turkish Journal of Gastroenterology, 2020)
-